CCSP Cert Prep: 6 Legal, Risk, and Compliance. - Chapple, Mike (linkedin.com, 2022)
Learn about legal, risk, and compliance issues in the world of cloud computing as you prepare for the Certified Cloud Security Professional (CCSP) exam.